Phytochemical screening and antimicrobial activity of crude extract of Tithonia diversifolia - Oloo Merciline; Menge Dominic (Open Journal of Biological Sciences - Peertechz Publications, 2020)
Tithonia diversifolia is a tropical woody herb or succulent shrub cultivated in many countries; it's an annual or perennial medicinal plant that has been a subject of research due to its various benefits in the treatment of different kinds of ailments. The aim of this study was to extract secondary metabolites from leaves, stems and roots of Tithonia diversifolia to evaluate their efficacy. Leaves, stems and roots of T. diversfolia were collected around Maasai Mara University and taken to laboratory for identification. The plant parts of interest were then washed dried for twenty-one days then were grounded into powder. The grounded powders were used to make concentrations by the use of distilled water, acetone and methanol as the solvents. Phytochemical screening was carried out to evaluate the presence of secondary metabolites which included test for tannins, saponins, terpenoids, alkaloids, glycocides, steroids and flavonoids. The extracts from leaves, stems and roots of T. diversofolia were investigated for antibacterial and anti-fungal activity on standard test organisms using agar disk-diffusion method. The use of punched filter papers dipped in the various concentrations were subjected into plates with nutrient agar containing standard test organisms e.g. Pseudomonas aeruginosa, Escherichia coli, Candida albicans and Staphylococcus aureus. The results for the phytochemical analysis of the extracts indicated the presence tannin flavonoids and alkaloids in all the plant parts and in all the solvents used. Results obtained from antimicrobial activity testing of crude extracts of T. diversifolia, showed variability in the inhibitory activity of T. diversifolia crude extracts against the test organisms. Among all the microorganisms used S. aureus is much more susceptible to the crude leaves extracts showing the highest inhibitory zone followed by methanolic extracts. The presence of these phytochemical and their ability to react against tests organisms indicates that the leaves, roots and stems of T. diversifolia could serve as basic ingredients in drug making for use in treatment of various ailments.